Planning Ahead for Better Neighborhoods: Long-Run Evidence from Tanzania - Michaels, Guy; Nigmatulina, Dzhamilya; Rauch, Ferdinand; Regan, Tanner; Baruah, Neeraj; Dahlstrand, Amanda (Journal of Political Economy, 2021)
Africa?s demand for urban housing is soaring, even as it faces a proliferation of slums. In this setting, can modest infrastructure investments in greenfield areas where people subsequently build their own houses facilitate long-run neighborhood development? We study Sites and Services projects implemented in seven Tanzanian cities during the 1970s and 1980s, and we use a spatial regression discontinuity design to compare greenfield areas that were treated (de novo) with nearby greenfield areas that were not. We find that by the 2010s, de novo areas developed into neighborhoods with larger, more regularly laid-out buildings and better-quality housing.